Symbolism and meaning in old masjid architecture of Malay archipelago: a case study of Masjid in Kerinci, Jambi, Indonesia - Abdul Rahim, Zaiton; Mohd Nawawi, Norwina; Denan, Zuraini; Abdul Majid, Noor Hanita; Abdullah, Fadzidah (Fatih Sultan Mehmet Vakif University Publication, 2019)
Masjid (mosque) plays a significant role in the life of a Muslim. Throughout history, the old masjids of the old cities and towns reflect the acculturation of Islamic faith with the local culture that embraced the religion. This paper demonstrates through experiential learning how acculturation of Islamic faith and culture of the people in the Malay Archipelago gives symbolic meanings to the masjid architecture and enhances the spatial as well as the spiritual experience of the people. The old masjid in the Kerinci region of Sumatra, Indonesia, was selected as the case studies. In the process of the research, important aspects of the religion and culture were encoded, presented and communicated in the form of architectural features of the masjid, giving meanings and heightened the spiritual experience of the users. The symbolic meanings made through architectural manifestation, in physical form, both structural and non-structural components of the masjid, enriches and gives a distinctive and unique character to the masjid architecture. The old masjid architecture of Kerinchi are simplified abstractions to manifest the worldview of the local people based on the spirit of Islam. The paper concluded that incorporating symbolism that does not impede Islamic teachings or the shariah but can enhance and even exalted the religious spirit of users while providing the distinct character to the masjid.